What Are You Voting For? Proximity to Refugee Reception Centres and Voting in the 2016 Italian Constitutional Referendum - Massimiliano Bratti; Claudio Deiana; Enkelejda Havari; Gianluca Mazzarella; Elena Claudia Meroni (Institute of Labor Economics (IZA), 2017)
In December 2016, in the middle of the "European refugee crisis", the Italian electorate voted for a referendum on crucial constitutional reform promoted by the governing party. The official aims of the reform were both to improve the country's governability and stability and to simplify the institutional setup. Despite not strictly being a political vote, as in the case of Brexit, the referendum was largely perceived as an assessment of the Prime Minister's work and the activity of his government. Using Italian municipality data, we provide novel empirical evidence on the impact of geographical proximity to refugee reception centres on voting behaviour. Our analysis demonstrates that being closer to refugee centres increased (1) the referendum turnout and (2) the proportion of anti-government votes. This evidence is consistent with the fact that the main opposition parties exploited the anti-immigration sentiments that were mounting in the population to influence people's voting. It also casts doubts on the political choice to put key decisions, such as changes in the Constitution of the Italian Republic (or leaving the European Union, as in the case of Brexit), to the popular vote at times when there are significant political emergencies to be faced.
Keywords: P16; R23; D72; 330; proximity; voting; refugee reception centres; referendum; Constitution; Italy